The Influence of User-Generated Content on Online Impulsive Buying Intention and Behavior : A Study of Generation Z - Sarah Tsabitah (MINOVa Ditria Jaya, 2025)
The rapid evolution of digital marketing has significantly altered the purchasing habits of younger consumers, particularly regarding spontaneous online transactions. This study investigated the influence of User-Generated Content on impulsive buying intention and subsequent impulsive buying behavior among Generation Z consumers of Wardah beauty products in Indonesia. Using a quantitative research design, data were collected through an online survey of 303 active social media users within the Generation Z demographic who had previously made purchases via e-commerce platforms. The structural model was analyzed using partial least squares structural equation modeling to examine the direct and indirect relationships between the variables. The results indicated that User-Generated Content exerted a positive and significant influence on impulsive buying intention. Furthermore, impulsive buying intention was found to be a significant predictor of actual impulsive buying behavior. These findings suggested that authentic peer-to-peer content, such as organic reviews and tutorials, functioned as a potent stimulus that triggered emotional responses, leading to unplanned consumption. The study concluded that for local cosmetic brands to effectively capture the Generation Z market, digital strategies should prioritize the facilitation and utilization of authentic content created by consumers rather than relying solely on traditional promotional materials. This approach enhanced social trust and emotional urgency, which were essential for driving conversion in a highly competitive digital marketplace.